Comparative Study between Capital Asset Pricing Model and Arbitrage Pricing Theory in Indonesian Capital Market during Period 2008-2012 - Leo Julianto (Department of Management, Faculty of Economics and Business, Brawijaya University, 2013)
For decades, there were many models explaining the returns earned emerged in order to fulfil the curiosity had by human. Since then, various studies and empirical findings in many countries’ stock market showedthat the empirical findings of market return explanation and the return of assets meet the different results in both clarify of model and identification of significant determinant variables.Therefore, many comparative studies between models were accomplished. In this study, the author attempts to do comparative study between two models, APT and CAPM, in Indonesian Capital Market during period 2008 until 2012. Besides, the author also attempts to find how much inflation, interest rate, and exchange rate describe the returns earned in each sector existed in Indonesia Capital Market. As the result, the author find out that CAPM has bigger explanation power than APT in Indonesian Capital Market during period 2008-2012. Besides, the author also found that among macroeconomic factors, there are only two macroeconomic factors that can affect certain samples significantly. They are change in BI rate, which affect AALI, ANTM, ASII, TLKM, UNTR, and change in exchange rate, which affect INDF and TLKM significantly.